Revealing a new fluorescence peak of the enhanced green fluorescent protein using three-dimensional fluorescence spectroscopy - Santos, Nathalia Vieira dos [UNESP]; Saponi, Carolina Falaschi [UNESP]; Greaves, Tamar Louise; Brandao Pereira, Jorge Fernando [UNESP] (Royal Soc Chemistry, 2019)
Fluorescent proteins have many applications as biomarkers and biosensors in the medical and biological fields. Their success was largely supported by modifications of the first isolated fluorescent protein, the wild-type Green Fluorescent Protein (wtGFP), which allowed the development of improved variants such as the Enhanced GFP (EGFP). The first reports on EGFP indicated that the protein presented a single form and fluorescence peak, in contrast to the two conformations observed in wtGFP. However, after experimental determination of the crystalline structure of EGFP, two conformations were found, generating questions regarding the relationship between EGFP structure and its spectral characteristics. To resolve the controversy, this study evaluated EGFP 3D fluorescence spectra at lower wavelengths and under distinct conditions (different concentrations, pH and temperatures), revealing the existence of a second fluorescence peak for this protein. It was possible to confirm that the new peak was not a reflection of the intrinsic fluorescence of proteins or an artefact from the 3D fluorescence spectroscopy. It was also shown that the second peak is pH dependent, sensitive to high temperatures and linearly related to EGFP concentration, confirming a direct relationship between the new fluorescence peak and EGFP protein structure. In addition to the revelation of the new EGFP fluorescence peak, this study demonstrated that 3D fluorescence can be used as powerful technique in the discovery of other elusive fluorophores.